Search for first generation scalar leptoquarks in pp collisions at √s=7 TeV with the ATLAS detector* - Aad, Georges; Anders, Christoph; Anders, Gabriel; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Kasieczka, Gregor; Khomich, Andrei; Kluge, Eike-Erik; et al. (Physics letters, 2012)
We report a search for first generation scalar leptoquarks using 1.03 fb−1 of proton-proton collisions data produced by the Large Hadron Collider at s=7 TeV and recorded by the ATLAS experiment. Leptoquarks are sought via their decay into an electron or neutrino and a quark, producing events with two oppositely charged electrons and at least two jets, or events with an electron, missing transverse momentum and at least two jets. Control data samples are used to validate background predictions from Monte Carlo simulation. In the signal region, the observed event yields are consistent with the background expectations. We exclude at 95% confidence level the production of first generation scalar leptoquark with masses mLQ<660(607) GeV when assuming the branching fraction of a leptoquark to a charged lepton is equal to 1.0 (0.5).
ATLAS Collaboration: G. Aad, C.F. Anders, G. Anders, V. Andrei, Y.Davygora, T.A. Dietzsch, C. Geweniger, P. Hanke, M. Henke, G. Kasieczka, A. Khomich, E.-E. Kluge, A. Kugel, V. Lendermann, R. Maenner, K. Meier, F. Mueller, R. Narayan, S. Poddar, S. Schaetzel, V. Scharf, S. Schmitt, A. Schöning, N. Schroer, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und weitere]
Gesehen am 30.11.2018